А rare case of alcohol septal ablation and cardioverter-defibrillator implantation in patient with Anderson-Fabry disease - M. Dimova; M. Gospodinova; K, Genova; E. Paskalev; V. Velchev (Българска кардиология)
Anderson-Fabry disease is a hereditary, X-linked disorder with multiorgan impairment. The debut of the disease is usually in childhood, the clinical course and the prognosis are determined by the degree of the heart, kidney and brain dysfunction. Cardiac involvement includes the development of hypertrophic cardiomyopathy, conduction disorders and less common - valvular disease. Among patients with hypertrophic cardiomyopathy, about 0.5-1% are due to Anderson-Fabry disease. We present a clinical case of a man diagnosed with Anderson-Fabry disease, the clinical suspicion of which was raised based on rapid progression of renal disease, lead to end-stage kidney failure, cerebrovascular disease, and hypertrophic cardiomyopathy. The patient underwent a successful kidney transplantation, and systemic treatment with enzyme replacement therapy, but despite this, the cardiac involvement progressed, necessitating the placement of an ICD and alcohol septal ablation of the first septal branch due to a severe subvalvular gradient.